Employment Assimilation of Immigrants - Evidence from Finland - Kari Hämäläinen; Aki Kangasharju; Sari Pekkala; Matti Sarvimäki (European Regional Science Association (ERSA), 2005)
This paper analyses economic effects of immigrants that moved to Finland be-tween 1990 and 2000. The focus is on labour market participation, which affects direct taxes paid and income transfers received by immigrants. Immigrants are followed from the year of immigration up to 2000 or out-migration. Countries of origin are grouped into four categories: OECD, neighbouring countries (Russia and Estonia), the "JIIS-countries” (i.e. former Yugoslavia, Iran, Irak and Soma-lia), and remaining other countries. The main result is that employment of immi-grants strongly increases over the years stayed in Finland. Consequently, non-humanitarian immigrants pay more direct taxes than they receive in income transfers after six years of immigration. When humanitarian immigration is in-cluded, the balance remains negative throughout the period of investigation. The analysis is based on immigrants staying in Finland for at least one year following immigration. Immigrants' use of public services and consumption are excluded from the analysis, due to data availability.
Keywords: 330